2008
DOI: 10.1590/s1413-86702008000400002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical evaluation of HIV-related lipodystrophy in an ambulatory population from the Hospital Universitário Cassiano Antonio de Morais, Vitória, ES, Brazil

Abstract: We designed a retrospective cohort study to identify factors associated with HIV-1 related lipodystrophy at a tertiary HIV-care center in Vitória, ES, Brazil. Inclusion criteria were documented HIV diagnosis, anti-retroviral therapy and age above 17 years. Highly active antiretroviral therapy (HAART) was initially the exposure variable, but a second analysis was also performed, as a nested case-control, based on the presence or absence of lipodystrophy. Use of protease inhibitors (PI) was associated with an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…Patient self-report on changes in body-fat distribution after HIV infection diagnosis associated with clinician examination was the most common method of lipodystrophy assessment in the studies reviewed (n=6) [18,19,23,[26][27][28] and that showed the greatest variation in prevalence rates, from 38.5% [26] to 67.9% [19]. Other methods used for lipodystrophy diagnosis in these studies were patient selfreport alone (n=4) [17,20,21,28]; clinician diagnosis associated with body measurements (n=1) [22]; patient self-report associated with body measurements (n=2) [30,31]; and clinician diagnosis alone (n=2) [24,25].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Patient self-report on changes in body-fat distribution after HIV infection diagnosis associated with clinician examination was the most common method of lipodystrophy assessment in the studies reviewed (n=6) [18,19,23,[26][27][28] and that showed the greatest variation in prevalence rates, from 38.5% [26] to 67.9% [19]. Other methods used for lipodystrophy diagnosis in these studies were patient selfreport alone (n=4) [17,20,21,28]; clinician diagnosis associated with body measurements (n=1) [22]; patient self-report associated with body measurements (n=2) [30,31]; and clinician diagnosis alone (n=2) [24,25].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Not all the surveyed patients developed lipodystrophy associated with HIV [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], which suggests that lipodystrophy syndrome varies not only with respect to the length of time of the treatment regimen, but also in relation to the effects of systemic chronic inflammatory process resulting from HIV infection itself and factors associated with lifestyle such as physical activity, dietary pattern, and other factors [23,36,37]. There are few studies in the literature comparing these changes with those of non-HIV-infected individuals, because a fat gain can happen with natural aging, or as an immune recovery process after initiation of HAART regimen [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations